Liberia : Enhanced Initiative for Heavily Indebted Poor Countries Initiative; Request for Additional Interim Assistance; and Press Release. (IMF Staff Country Reports; Country Report, 2010)
This paper reviews the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC) Initiative for Liberia. Performance under the Extended Credit Facility (ECF)-supported program is solid. The third ECF review was completed on a lapse of time basis on December 18, 2009. All but one of the quantitative performance criteria (PC) for the end-June 2009 test date were observed. The PC on total revenue collection was not observed but the deviation was temporary and did not jeopardize program objectives. Structural reform commitments were largely met, though some with delays.